Desain Pembelajaran Berbasis Daring pada Masa Covid-19 di SDN Kunciran 03 - Fathya, Nisrina Nur; Widiani, Uci; Apriola, Nabilla Putri; Denabila, Esa (Lembaga Yasin AlSys, 2022)
This research highlights the importance of applying online learning design to basic education to make the learning process more effective. This research also intends to explore online learning to achieve educational goals. This study uses qualitative phenomenological research to find out how online and offline learning is applied in one of SDN Kunciran 03. Online learning is learning that is done online or indirectly using the use of computing devices or gadgets that can be connected, to each other and students can use these media to communicate. From the results of the study, there are several obstacles in the implementation process, but teachers can overcome them well to educate students. Overall, the implementation of learning during the pandemic has had a positive impact on the sustainability of education in countries, but several factors need to be considered so that the learning process is more effective during the pandemic, therefore several recommendations have been formulated for further research.